Postharvest Hot Water Treatment Followed by Chitosan- and κ-Carrageenan-Based Composite Coating Induces the Disease Resistance and Preserves the Quality in Dragon Fruit (Hylocereus undatus). (21st September 2020) - Nguyen, Hanh Thi; Boonyaritthongchai, Panida; Buanong, Mantana; Supapvanich, Suriyan; Wongs-Aree, Chalermchai
ABSTRACT: Abstract: Postharvest diseases and loss of freshness are major problems that cause the deterioration of dragon fruit. The present study determined the effect of hot water treatment (HWT) at 50°C for 5 min followed by 1.0% chitosan and 0.2% κ-carrageenan-based composite coating to counter the issues. The results showed that HWT followed by the composite coating-enhanced antioxidant enzyme activities and reduced accumulation of H2 O2 in the peel, which demonstrated the defensive response in the tissues leading to reduce disease development. The chitinase and β-1, 3-glucanase did not show a significant effect in reducing the postharvest diseases of dragon fruit. While the HWT helped to increase phenolics content and antioxidant capacity in the pulp, the composite coating was crucial to maintain green color of the bract. Therefore, we concluded that HWT combined with composite coating controlled the diseases via antioxidant defensive response and maintained the overall quality of dragon fruit for 30 days of storage at 10°C.